Strategi Pengelolaan Budidaya dalam Industri Udang: Tinjauan Produktivitas Budidaya Udang - Ayu Sahira Ramadhani; Nova Pebi Rachmawati br. Sembiring; Wien Kuntari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Vannamei shrimp marketing and cultivation strategies highlight how entrepreneurs can take advantage of existing strengths and opportunities to maximize profits and business growth. Through SWOT analysis, the proposed strategy includes increasing seed production and quality, recruiting experts to increase production and promotion, as well as managing threats and weaknesses with effective strategies. This strategy aims to optimize market segmentation, targeting, positioning and marketing mix, with an emphasis on the importance of adapting to changing business conditions and active support from the government in overcoming regulatory obstacles. This study explores the economic and social impacts of vannamei shrimp farming in Ivory Coast villages, identifying factors that contribute to community well-being, including access to resources, work ethic, and economic motivation, as well as challenges faced, such as lack of financial support from local government . The recommendations given emphasize the importance of government support, improving farmer skills, and further research focusing on the welfare of shrimp farm workers. By implementing effective marketing strategies and paying attention to sustainable development and utilization of coastal and marine resources, this research proposes that vannamei shrimp cultivation can not only develop but also contribute significantly to the economic and social welfare of society.